2020
DOI: 10.21203/rs.3.rs-49031/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Prevalence of HPV Infection in Head and Neck Cancer Patients in Egypt: National Cancer Institute Experience.

Abstract: Background: The new classification of Head and Neck Squamous Cell Carcinoma (HNSCC) according to their association with human papillomavirus (HPV) infection into HPV positive tumors with good prognosis and HPV negative tumors with poor prognosis has changed the treatment strategy of HNSCCs dramatically worldwide. However, data concerning HPV infection in HNSCCs patients is still limited and there are no studies regarding HPV genotypes in HNSCC among Egyptians. Therefore, the aim of the current study is to inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…1 Head and Neck Squamous Cell Carcinomas, include cancers of the aero-digestive tract, an estimated annual burden of thousands of deaths, and more than 650,000 incident cases, making it the sixth most common cancer worldwide, studies have shown that Head & Neck Squamous cell carcinomas (HNSCCs) responsible for about 20% of all cancers. 2,3 In Egypt, the Cancer Pathology Registry of the National Cancer Institute of Cairo University declared that during the years 2003/2004 laryngeal cancer was the most frequent among all respiratory cancers (27.84%) and the tenth most frequent among all cancers (1.77%), with most cases diagnosed at advanced stages. 4,5 Laryngeal cancer can result from the combined action of smoking, drinking alcohol, air pollution, and gastroesophageal reflux.…”
Section: Introductionmentioning
confidence: 99%
“…1 Head and Neck Squamous Cell Carcinomas, include cancers of the aero-digestive tract, an estimated annual burden of thousands of deaths, and more than 650,000 incident cases, making it the sixth most common cancer worldwide, studies have shown that Head & Neck Squamous cell carcinomas (HNSCCs) responsible for about 20% of all cancers. 2,3 In Egypt, the Cancer Pathology Registry of the National Cancer Institute of Cairo University declared that during the years 2003/2004 laryngeal cancer was the most frequent among all respiratory cancers (27.84%) and the tenth most frequent among all cancers (1.77%), with most cases diagnosed at advanced stages. 4,5 Laryngeal cancer can result from the combined action of smoking, drinking alcohol, air pollution, and gastroesophageal reflux.…”
Section: Introductionmentioning
confidence: 99%